Pengembagang Modul Bahasa Inggris untuk Mahasiswa Program Studi Matematika di STKIP Muhammadiyah Pagaralam - Sari, Andini; Yuliana (Jurnal Korpus, 2022)
The purpose of this study is to develop an English module based on local wisdom for students that is in accordance with the needs analysis. This module is expected to facilitate the teaching of English to students of non-English study programs at STKIP Muhammadiyah and improve the achievement of learning outcomes through modules made based on the Borg &Gall development scheme by going through several stages, namely (1) needs analysis (2) module planning (3) module development (4) module validation (5) module revision I (6) module trial (7) module revision II (8) final module. The method used in this study is Research and Development. Research that uses this research and development design has test subjects in the form of; 2 learning experts, 2 peers, and 40 1st semester students who took English courses and were chosen randomly as validation of the module test. Data were collected through observations, interviews and questionnaires that were shared with the test subjects and became a reference for module development according to the stages adapted from the Borg&Gall development scheme. The results of the development of this module are in the form of teaching materials that can be used as the main reference in teaching English in the Mathematics study program at STKIP Muhammadiyah Pagaralam.